Cidadania, informação e consumo: a internet na formação do cidadão-consumidor da era do comércio eletrônico - Marco Antonio Fernandes Frade (2002)
It verifies the concepts of citizenship and information relating them with the practice of consumption in the contemporary globalized societies. The object of study that justifies the assumed premises is the electronic commerce, its technological features and market strategies. For the data collection, were used interviews in depth with specialists of the electronic commerce area to investigate some questions considered relevant, including: a) the determinism of the capitalist societies, which are guided to consumption; b) the usage of information as the main attractive to consumers in the electronic commerce sites; c) the changes in characteristics and objectives of internet towards the determinism of consumption, observed from the enormous and fast growth of audience and the volume of business actually made in the sites of electronic commerce. Another method utilized was the documental search, predominantly the primary and secondary sources, as well as reports and analyses from research institutes that follows the market and audiences behavior of Internet in Brazil. It concludes that the Internet is today the communication channel that privileges the usage of information to reaffirm the vocation for consumption of the citizens that access the network. Vocation that can be extended to all spheres of the life of the citizen who participates, even if not voluntarily, of the capital hegemony, politics that was aggravated with the enlargement of the globalization process that was imposed to the contemporary world.